LANGUAGE LEARNING STRATEGY TAXONOMY USED BY THE TEACHER IN TEACHING ENGLISH - Trisna Dinillah Harya (State Institute for Islamic Studies IAIN of Metro, 2016)
Language Learning Strategies is simply refers to an individual‘s approach to complete a task. This is an individual way of organizing and using a particular set of skills in order to learn content or accomplish other tasks more effectively and efficiently in school as well as in nonacademic settings. Some previously conducted research found that good language learners actively involve themselves in the language learning process by identifying and seeking preferred learning environments and exploring them. The newly adapted curriculum in Indonesia emphasizes on the discovery learning. This study is aimed to find facts dealing with learning strategies used by high achievers and underachievers, whether there are any differences between the two groups. After research was conducted, the data shows that there are some differences in the learning strategies used by the two groups. The high-achievers uses more varied strategies.